RANCANG SISTEM INFORMASI ARSIP DINAMIS IN-AKTIF DI LINGKUNGAN SETDA PROVINSI JAMBI - Irma Suana (JURNAL AKADEMIKA)
The creation of good archival condition must be supported by a number of factors such as: the existence of an adequate system of record keeping , personnel are professional in the field of archives and take advantage of technological advances in the field of archives effectively and efficiently . However, in practice there are problems that occur , such as: less optimal handling records both active and in- active Sub administration , archives and public agencies Setda ekspedidi in Jambi province due to the lack of specialized personnel who are given tasks and responsibilities both in processing unit as well as archival unit to deal with issues related to archives , facilities and infrastructure for archival storage in active dinamiis not used optimally , lack of awareness among employees of the importance of archives as high information in the implementation of day-to- day administration , it is seen from these archives are still stacked on the desk . Based on the description outlined above , the authors are interested in doing the writing with the title " Design Information Systems Dynamic In - Active Records in Environmental Secretariat Jambi " .